The Vietnam War from the Other Side, 1st edition - Cheng, Guan Ang (Routledge, 2020)
Existing studies of the Vietnam War have been written mostly from an American perspective, using western sources, and viewing the conflict through western eyes. This book, based on extensive original research, including Vietnamese, Chinese and former Soviet sources, presents a history of the war from the perspective of the Vietnamese communists. It charts relations with Moscow and Beijing, showing how the involvement of the two major communist powers changed over time, and how the Vietnamese, despite their huge dependence on the Chinese and the Soviets, were most definitely in charge of their own decision making. Overall, it provides an important corrective to the many one-sided studies of the war, and presents a very interesting new perspective.